2018
DOI: 10.1016/j.jce.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of institutional volatility on financial volatility in transition economies

Abstract: What have been the determinants of financial volatility in the transition countries of Central and Eastern Europe and the former Soviet Union? This paper posits that institutional changes, and in particular the volatility of crucial institutions such as property rights, have been the major causes of financial volatility in transition. Building a unique monthly database of 20 transition economies from 1991-2017, this paper applies the GARCH family of models to examine financial volatility as a function of insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 126 publications
1
28
0
Order By: Relevance
“…A change of political institutions can engender the largest amount of uncertainty and, at the same point, effectively change the rules of the game going forward (Hartwell, ). If the formal party system is abolished and one‐party rule is instituted, then political connections become crucial for nearly every form of business decision (Boubakri, Cosset, & Saffar, ); moreover, given that firms tends to associate with other politically like‐minded firms (Stark & Vedres, ), the disruption of carefully cultivated inter‐business networks may also have a severe disrupting effect on firm operations.…”
Section: Why Populism and Institutions Matter In Strategymentioning
confidence: 99%
“…A change of political institutions can engender the largest amount of uncertainty and, at the same point, effectively change the rules of the game going forward (Hartwell, ). If the formal party system is abolished and one‐party rule is instituted, then political connections become crucial for nearly every form of business decision (Boubakri, Cosset, & Saffar, ); moreover, given that firms tends to associate with other politically like‐minded firms (Stark & Vedres, ), the disruption of carefully cultivated inter‐business networks may also have a severe disrupting effect on firm operations.…”
Section: Why Populism and Institutions Matter In Strategymentioning
confidence: 99%
“…The financial volatility has different sources, related to economic conditions, institutional issues or market uncertainty (Hartwell, 2018). Macroeconomic announcements also affect the financial volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies found that institutions has significant contribution on financial inclusion in various ways such as Zins & Weill (2016), Okello, Ntayi & Munene (2017, Hartwell (2017), Leroy &Pop (2018), andWilliams (2018). Zins & Weill (2016) report some African countries still face low level of financial inclusion.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331 184mentioning
confidence: 96%
“…This is addressed to reduce the transaction gap and financial literacy between cities and villages, between low and high-income people. Hartwell (2017) adds some indicators of institutions such as property right and democracy can encourage the financial volatility in Central and Eastern Europe and the former Soviet Union. The democracy indicator was also utilized by Williams (2018) to examine the linkage between credit market and economic growth in emerging and developing economies.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331 184mentioning
confidence: 99%